11th IEEE International Conference on Engineering of Complex Computer Systems (ICECCS'06)
DOI: 10.1109/iceccs.2006.1690358
|View full text |Cite
|
Sign up to set email alerts
|

Engineering emergence

Abstract: We explore various definitions and characteristics of emergence, how we might recognise and measure emergence, and how we might engineer emergent systems. We discuss the TUNA ("Theory Underpinning Nanotech Assemblers") project, which is investigating emergent engineering in the context of molecular nanotechnology, and use the TUNA case study to explore an architecture suitable for emergent complex systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…The question whether a system's macroscopic state is really new or whether it is defined on the micro-level already before the instantiation stays unanswered. As discussed by Stepney et al [11]: How could anything new actually emerge from something that is already existent? However, Bickhard and Campbell [12] argue that this question is ill-posed.…”
Section: Emergencementioning
confidence: 99%
“…The question whether a system's macroscopic state is really new or whether it is defined on the micro-level already before the instantiation stays unanswered. As discussed by Stepney et al [11]: How could anything new actually emerge from something that is already existent? However, Bickhard and Campbell [12] argue that this question is ill-posed.…”
Section: Emergencementioning
confidence: 99%
“…In line with the paradigm of complexity engineering, Systems Aikido [5] is a suggestion to use a system's intrinsic dynamic behaviour in pursuit of the researcher's goal. Also [6] argued in favour of engineering systems with emergence, and illustrated this with so-called nanites, which are nanoscale robots that build micro-scale artefacts, based on local rules. No matter how large or small the system, the underlying idea is mainly to use the mechanisms of Complex Adaptive Systems (CAS) in favour of the engineer's objective [7,8].…”
Section: A U T H O R C O P Ymentioning
confidence: 99%
“…6 Chemical compositions have been found that exhibit life-like characteristics including "cells" (or rather, blobs or bubbles) separating, merging, interacting, pulsating and moving through chemotaxis. A potential application for protocells is the "Future Venice" project 7 : the idea is that protocells use substances available in the water or air to self-assemble and build "living" structures that dynamically reinforce the existing old ones, such as walls and piles.…”
Section: Artificial Chemical Lifementioning
confidence: 99%
See 1 more Smart Citation
“…In [16] we provide a review of opinion on emergence. We start from Ronald et al's definition of emergence: "The language of design L 1 and the language of observation L 2 are distinct, and the causal link between the elementary interactions programmed in L 1 and the behaviors observed in L 2 is non-obvious to the observer-who therefore experiences surprise."…”
Section: Background: Emergencementioning
confidence: 99%